SIKAP REMAJA TERHADAP SEKS PRANIKAH - , DEBY IFKE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Many cases ofpremaritalsexamong adolescentswere due to lackof moraleducationand the negative influenceofthe environment. The subjects of this research wereadolescentsat12 to 18 years old live in thecity ofBalikpapan. The numbers of early adolescentsat 12 to 14years old are 390 and middle adolescents at 15 to 18 years old are 196. The instrument were used in this research is the scale of adolescentsâ attitude toward premarital sex. Three factorial of Analysis of Varian were used to analyze this research. The results of this research show that there was no interaction over three variables like location of residence, stage of development and also gender. But there were an interaction over the adolescentsâ stage of development and gender.The conclusion of this research is more of adolescents attitude toward premarital sex were in low category. Adolescents who live incoastal area were higher in the attitude of premarital sex than adolescents who livein urban areas. The attitudes of middle adolescents toward premarital sex were higher than early adolescents. And boysâattitudes toward premarital sex were higher than girls.